Kenya commodity price report - July 2021 - Chepchirchir, Ruth T.; B. J. K, Maina (International Food Policy Research Institute, 2021)
The Food Price Monitor: Kenya is a monthly report developed for the Food Security Portal (FSP), facilitated by IFPRI, with the goal of providing clear and accurate information on commodity price trends and variations in selected markets throughout Kenya. The reports are intended as a resource for those interested in agricultural commodity markets in Kenya, namely producers, traders, consumers, or other agricultural stakeholders.